Content Creative Marketing Strategy in Increasing Rural Agribusiness Competitiveness: Case study of Kopi Saung Desa in Kalirejo sub-district, Central Lampung Regency - Pradika, Daffa Alsa; Fitriani, Fitriani; Wandira, Vidia Ayu (Journal of Food System & Agribusiness, 2024)
The development of agribusiness is an important trigger in improving the regional economy, especially in the rural agricultural sector.  The trend of coffee consumption in Indonesia is growing along with lifestyle developments. This is a very promising business opportunity for coffee business people, especially in coffee production centers in Indonesia. This research aims to analyze the effectiveness of creative content marketing strategies in increasing the competitiveness of rural agribusiness businesses with a case study of the Saung Kopi Village UKM in Central Lampung Regency. The research uses a case study approach with in-depth interview methods and qualitative and quantitative data analysis through questionnaire instruments. The research results show that agribusiness actors in Central Lampung face challenges in conventional and digital marketing. Effective marketing strategies via social media, such as Instagram, have been proven to increase engagement rates and reach a wider audience. A creative content marketing approach can increase brand awareness, expand market reach, and support the sustainability of rural agribusiness businesses.